Determinant of Workload, Burnouts and Transformational Leadership on Employees’ Performance Moderated by Work Life Balance at Aviation Industries - Iswandir Iswandir; Dewi Puspaningtyas Faeni (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to investigate the correlations among variables;  workload, burnout, and transformational leadership on employees’ performance, mediated by work–life balance variable. The type of research is a quantitative, with as much as 240 respondents from total of 1,956 employees. The population of this research is Aviation Industries employees. This research was analyzed by using SmartPLS 4.0 (PLS-SEM). Results of this research is tha workload, burnout, and transformational leadership have significant direct effects on employees’ performance. Whereas, work–life balance has a significant role in the correlations mediating workload and performance, burnout and performance, as well as transformational leadership and performance. The model explains indicating moderate to strong explanatory power. By demonstrating the strategic importance of work-life balance in connecting leadership practices to performance results, these findings expand the Job Demands-Resources (JD-R) paradigm. Findings from this research can help aviation companies improve worker productivity through better workload management, less burnout, and more transformational leadership within a framework that encourages a healthy work-life balance.   Keywords: workload; burnout; transformational leadership; work–life balance; employees’ performance.